Leaflet-Based Health Education and Its Effect on Adolescent Mental Health Empowerment - Mutmainnah, Awalia; Susilawaty, Andi; Aswadi, Aswadi (Unihealth Community Research, 2026)
Adolescent mental health is a growing public health concern, particularly in school environments where students experience significant academic and social pressures. Limited mental health literacy among adolescents may increase vulnerability to stress, anxiety, and emotional problems, which can adversely affect learning achievement and psychological well-being. This study presents a community-based empowerment approach by utilizing leaflet media as an educational intervention to improve mental health literacy among adolescents. The objective of this study was to analyze the mental health situation of adolescents and to evaluate the effectiveness of leaflet-based mental health education as a community empowerment strategy at SMP Negeri 1 Tapalang. A quasi-experimental method with a one-group pre-test and post-test design was applied. The participants consisted of 30 junior high school students. The intervention involved structured mental health education delivered through leaflet media. Data were collected using a validated knowledge questionnaire and analyzed using statistical software, including the Shapiro–Wilk test for normality and the paired sample t-test for comparison. The findings revealed a significant improvement in students’ mental health knowledge following the intervention. The mean pre-test score increased from 56.40 to 78.90 in the post-test, with a statistically significant result (p < 0.05). These results indicate that leaflet-based education is an effective and practical medium for enhancing adolescent mental health literacy and supporting community empowerment initiatives within the school setting.